2018
DOI: 10.1017/s0714980818000442
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Discharge Decisions Concerning Older Patients: Understanding the Underlying Process

Abstract: RÉSUMÉL’hospitalisation des personnes âgées s’accompagnent d’un risque de déclin fonctionnel, et d’une grande fréquence de réadmission. Nous avons cherché à comprendre les processus de prise de décisions cliniques qui influencent l’orientation des patients âgés après leur sortie de l’hôpital. Les procédures déterminant l’orientation d’un patient âgé après une hospitalisation en service aigu ne sont pas claires. Nous avons comparé les décisions d’orientation (retour à domicile ou maison de retraite) réalisées p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…In addition, another study confirmed that older patients’ PLOS (>17 days) was associated with discharge to places other than usual residence [ 49 ]. Indeed, hospitalizations are frequently associated in older people with an increased risk of functional decline both during hospitalization and following discharge [ 50 ]. These findings provide a rationale for increased staffing for elderly patients requiring intensive care in hospitals, particularly for those with cognitive impairment and multiple comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another study confirmed that older patients’ PLOS (>17 days) was associated with discharge to places other than usual residence [ 49 ]. Indeed, hospitalizations are frequently associated in older people with an increased risk of functional decline both during hospitalization and following discharge [ 50 ]. These findings provide a rationale for increased staffing for elderly patients requiring intensive care in hospitals, particularly for those with cognitive impairment and multiple comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies analyze the decision-making process from a hospital's perspective showing the relevance of hospital-level factors like quality of the discharge management. But these studies do not focus on the social situation of the patients [e.g., ( 12 , 23 , 24 )]. There exists a broad range of studies as well as meta-analyses on the question of social predictors of nursing home admissions or institutionalizations in the general population ( 10 , 14 , 25 – 28 ).…”
Section: Introductionmentioning
confidence: 99%